Hubungan Efikasi Diri dan Penguasaan Gaya Bahasa dengan Kemampuan Apresiasi Novel - Wulan Febrina (Program Studi Magister Linguistik Terapan UNJ, 2017)
The objective of this research was to find out the correlation between self-efficacy and language style mastery with novel appreciation ability either partially or simultaneously. This research was conducted at eight grade of SMAN 8 Bengkulu in 2015. The samples of this research were 40 students by using simple random sampling. This research used correlational method between X and Y variables. The data were analyzed by using regression and correlation analysis. The result of this research indicate that (1) there is a positive correlation between self- efficacy with novel appreciation ability with correlation coefficient is 0.694 and determination coefficient is 69, 4%, it has regression equation Y = -46,766 + 1,023 X1 (2) there is a positive correlation between language style mastery with novel appreciation ability with correlation coefficient is 0.53 and determination coefficient is 53%, it has regression equation Y = 40,.339 + 1,776 X2 (3) there is a positive correlation between self-efficacy and language style mastery all together with novel appreciation ability. Based on the result of the research, the researcher concluded that novel appreciation ability can be improved by increasing self-efficacy and language style mastery with correlation coefficient is 0.801 and determination coefficient 80.1%, it has regression equation Y = -33.970 + 0,762 X1 +0,945 X2..